The Effect of Online Games on Behavior Phubbing Students - Dewi, Fresa Ruwita (Asosiasi Asesmen Pendidikan (AAP), 2024)
The aim of this research is to find out whether there is an influence of online games on phubbing behavior and aims to see a picture of online games and students' phubbing behavior. The method used in this research uses a quantitative approach. The population and sample in this research were 161 students at Yapeni Citeureup Bogor Middle School. Data analysis used SPSS version 29 software with simple linear regression techniques. The findings in this research are that there is a significant influence of online games (X) on phubbing behavior (Y), seen from the contribution made by online games of 32.9% to phubbing behavior. The influence of the level of online games and phubbing behavior is in the high influence category with a significant value of 0.326%, so it can be stated that the increase in online games causes phubbing behavior.